“Implementación de un generador solar foto voltaico de un kilovatio con medidor bidireccional para determinar el ahorro energético en el bloque “B” de la Universidad Técnica de Cotopaxi extensión La Maná”. - Tacurid Pinela, Kevin Bryan (2022)
This project presents the proposal for the implementation of a photovoltaic solar generator of one kilowatt with a bidirectional meter to determine energy savings in block "B" of the Technical University of Cotopaxi, La Maná extension. The proposed photovoltaic solar generation system consists of the energy generation stage and the projection with which it will contribute to the monthly reduction of electrical energy consumption, as well as the reduction of the billing payment of the same. The photovoltaic solar generation system is a type of installation in which elements such as: photovoltaic panels, solar microinverter, solar panel meter, a bidirectional meter and the power line of the network are involved. The photovoltaic solar generator is connected to the bidirectional meter through the solar inverter, injecting the energy produced into it. This thesis studies the sizing, design, implementation and maintenance of a one kilowatt photovoltaic solar generation system with a bidirectional meter, to determine energy savings in block "B" of the Technical University of Cotopaxi, La Maná extension. It is intended that the entire photovoltaic solar generation system function as a laboratory for the electromechanical engineering career and put into practice the knowledge acquired in matters such as Industrial maintenance, electrical circuits and Renewable Energies.